Angiotensin-(1-7) stimulates the phosphorylation of Akt in rat extracardiac tissues in vivo via receptor Mas - Muñoz, Marina Cecilia (2010)
The in vivo effect of angiotensin (ANG)-(1-7) on the activation of insulin signaling transduction in rat extracardiac tissues is unknown. Thus, in the present study, we evaluated the ability of ANG-(1-7) to stimulate the phosphorylation of Akt, a main mediator of insulin action in rat extracardiac tissues (adipose tissue, liver and skeletal muscle). We proved that ANG-(1-7) induces the phosphorylation of Akt at both threonine 308 and serine 473 in all tissues analyzed. Selective antagonism of the Mas receptor with A779 blocked the ANG-(1-7)-induced Akt phosphorylation in extracardiac tissues. Reinforcing this evidence, we determined that ANG-(1-7) induces the in vivo activation of the downstream target of Akt, glycogen synthase kinase-3β in liver and skeletal muscle. Moreover, in every tissue analyzed, the presence of the Mas receptor was detected by immunohistochemical analysis. Based on the current results, we postulate that ANG-(1-7) could be a positive physiological contributor to the actions of insulin in extracardiac tissues. Therefore, our findings extend the possibilities for new approaches in the study of ANG-(1-7)/Mas receptor axis and show the therapeutic potential of ANG-(1-7) in the treatment of metabolic disorders such as insulin resistance as well as other disorders associated with diminished Akt activity.